A review of railway sanding system research: adhesion restoration and leaf layer removal. (2nd October 2018) - Skipper, William A.; Chalisey, Anup; Lewis, Roger
ABSTRACT: This paper aims to provide a comprehensive review into academic and industrial research concerning the use of particles as a means of recovering adhesion when low adhesion conditions exist within the wheel/rail contact. The most common particle used is sand, generally possessing a high silica content, usually between 0.85 and 1.4 mm in size. Sand is currently being applied in low adhesion conditions in two ways: firing the sand into the wheel/rail contact by means of a train-borne sanding system, or by suspending it in a gel and applying it to the rail head with either a train-borne system or using a wayside applicator. Sanding has been used for a long time, but little research has been conducted on the sanding system, with research shortfalls surrounding particle properties and models of the mechanical behaviour of the particles' effect in the wheel/rail contact. This paper includes a gap analysis method whereby previous research has been categorised based on seven criteria, designed to help assess the papers. The research was then graded as either 'A', 'B' or 'C' with 'A' grade research representing peer-reviewed work conducted across a range of scales or with an aspect of modelling. Most academic research was of 'B' grade due to the lack of multiple scales or modelling, which was also lacking in industrial research, but due to the lack of peer review most industrial research received a 'C' grade. The review also found there was evidence to suggest a lack of linkage between academia and industry with regards to taking sanding research findings forward. Additionally, this review helps clarify what future work is needed to optimise the sanding system to best recover adhesion and remove lubricating layers in the wheel/rail contact.